Recent Progress in Emerging Near-Infrared Emitting Materials for Light-Emitting Diode Applications - Zheng, Yingqi; Zhu, Xiaozhang (Organic Materials, 2020)
In view of the wide applications of near-infrared (NIR) light in night vision, security, medicine, sensors, telecommunications, and military applications, and the scarcity of high-efficiency NIR-emitting materials, development of alternative NIR-emitting materials is urgently required. In this review, we focus on three kinds of emerging NIR-emitting materials used in light-emitting diodes (LEDs), namely organic materials, inorganic quantum dot (QD) materials, and organic–inorganic hybrid perovskite materials; the corresponding devices are organic LEDs, QD LEDs, and perovskite LEDs. The advantages and disadvantages of the three kinds of materials are discussed, some representative works are reviewed, and a brief outlook for these materials is provided.
Keywords: near-infrared emitting materials; materials design; organic light-emitting diodes; perovskite light-emitting diodes; quantum dot emitting diodes